2022
DOI: 10.1038/s41467-022-34588-9
|View full text |Cite
|
Sign up to set email alerts
|

A widespread group of large plasmids in methanotrophic Methanoperedens archaea

Abstract: Anaerobic methanotrophic (ANME) archaea obtain energy from the breakdown of methane, yet their extrachromosomal genetic elements are little understood. Here we describe large plasmids associated with ANME archaea of the Methanoperedens genus in enrichment cultures and other natural anoxic environments. By manual curation we show that two of the plasmids are large (155,605 bp and 191,912 bp), circular, and may replicate bidirectionally. The plasmids occur in the same copy number as the main chromosome, and plas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Analysis of the metagenome-assembled genome (MAG) from the in-house "Ca. Methanoperedens BLZ2" strain revealed the presence of one putative ACS-encoding gene and one ACD-encoding gene (16,33). For a MAG from ANME-2a, three putative ACS-encoding genes were found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the metagenome-assembled genome (MAG) from the in-house "Ca. Methanoperedens BLZ2" strain revealed the presence of one putative ACS-encoding gene and one ACD-encoding gene (16,33). For a MAG from ANME-2a, three putative ACS-encoding genes were found.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptome analysis of the "Ca. Methanoperedens BLZ2" biomass grown in bioreactors fed with nitrate and methane (33) showed that ACS and ACD of ANME-2d were expressed at 20 and 40 transcripts per million (TPM), respectively, which are about one-half the values of the nitrate reductase genes narA (79 TPM) and narB (109 TPM) as well as the F 420 -dependent methylene-tetrahydromethanopterin (H 4 MPT) reductase gene mer (75 TPM) and the methenyl-H 4 MPT cyclohydrolase gene mch (65 TPM), which encode enzymes that are required for reverse methanogenesis. ACS and ACD of ANME-2d were also previously detected in the proteome of ANME-2d (9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While these alone are larger than many typical plasmids and viral genomes, megaplasmids have been reported in Methanosarcinales (the taxonomic order containing the organisms in this study) and are common in Haloarchaea ( 83 ). Additionally, extrachromosomal elements up to 1 Mb known as borgs ( 56 ) and unusually large plasmids up to 200 kb ( 84 ) have recently been identified in Methanoperedens spp. (ANME-2d) and proposed to act as gene transfer agents, including of large MHCs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on gene content and co-occurrence patterns, Borgs associate with several species of anaerobic methanotrophic (ANME) archaea of the Methanoperedens genus [ 3 ]. A search for other ECEs associated with these archaea also led to the recent discovery of large plasmids found in members of the same genus, yet a distinct clade of Methanoperedens species [ 4 ].…”
Section: Introductionmentioning
confidence: 99%